Workshop Media Pembelajaran Interaktif Berbasis Audio-Visual untuk Meningkatkan Kompetensi Guru di Era Abad 21 - Suryani, Ani Wilujeng; Larasati, Ika Putri; Ambarwati, Ferdiana; Novelita, Ferina; Pradiana, Fika (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
In the 21st century, the rapid development of technology requires teachers to employ a range of digital devices to assist the learning process. Nevertheless, there are still many teachers who lack proficiency in digital technology due to their ongoing struggle with its use. The objective of this community service activity is to enhance the proficiency of teachers at MAN 2 Mojokerto in creating and developing educational materials/media that align with the characteristics of today's students, through the use of diverse digital technologies. The activity comprises three distinct stages: the preparatory stage for problem identification, the hybrid workshops stage, and the evaluation phase involving the satisfaction survey questionnaire at the conclusion of each workshop session. According to the findings of the satisfaction survey, the majority of teachers expressed contentment with all instructional materials that were delivered during the workshop. Furthermore, the pre-test and post-test scores of the workshop participants also showed the successful enhancement of instructors' comprehension and proficiency at MAN 2 Mojokerto in using audio-visual-based interactive learning media.